2021
DOI: 10.1177/00368504211010581
|View full text |Cite
|
Sign up to set email alerts
|

Effect of conglomeration gradation on loess shear strength with different water content

Abstract: Particle gradation and water content are important factors affecting shear strength of soil. However, due to chemical cementation and molecular attraction, loess particles commonly stick together forming conglomerations. Till date, the superposition effect of water content and conglomeration gradation on loess shear strength has rarely been studied and undeniably requires further systematic explorations and development. In this study, loess samples were prepared with three conglomeration gradations and five wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…de Dios Herrero et al (2020) revealed the relationship between the collapse index and PSD, with the letter increasing with uniform coefficient C U . Furthermore, Kong et al (2021) proved that the effect of sand PSD on shear strength decreases as the water content increases. The rheology, soil–water properties and other hydraulic characteristics of loess are also reported to be affected by changes in the PSD (Bai et al, 2020; Huang et al, 2015; Qiao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…de Dios Herrero et al (2020) revealed the relationship between the collapse index and PSD, with the letter increasing with uniform coefficient C U . Furthermore, Kong et al (2021) proved that the effect of sand PSD on shear strength decreases as the water content increases. The rheology, soil–water properties and other hydraulic characteristics of loess are also reported to be affected by changes in the PSD (Bai et al, 2020; Huang et al, 2015; Qiao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The internal friction angle of loess decreases with increasing water content (Luo et al, 2014;Wang et al, 2014;Zhou et al, 2018a;Tian et al, 2021). Additionally, the internal friction angle of loess increases with increasing dry density (Zhou et al, 2018a;Kong et al, 2021;Guo et al, 2021). The internal friction angle of loess is influenced by freeze-thaw cycles, and the results of these studies are different.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars at home and abroad have done a lot of work on the impact of grain size composition on other soil engineering properties [26][27][28][29][30]. Thevanayagam and Mohan [31] studied the influence of fine grain content on the engineering properties of sand, and proposed to describe the stress-strain relationship of sand by using the inter particle void ratio and state parameters.…”
Section: Introductionmentioning
confidence: 99%